2018
DOI: 10.1002/tafs.10053
|View full text |Cite
|
Sign up to set email alerts
|

Dam Removal and Fish Passage Improvement Influence Fish Assemblages in the Penobscot River, Maine

Abstract: Dams and their impoundments disrupt river habitat connectivity to the detriment of migratory fishes. Removal of dams improves riverine connectivity and lotic habitat, which benefits not only these fishes but also resident fluvial specialist species. Restoration efforts on the Penobscot River, Maine, are among the largest recently completed in the United States and include the removal of the two lowermost dams and improvements to fish passage at several remaining barriers. We assessed fish assemblages in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 41 publications
(100 reference statements)
2
37
0
Order By: Relevance
“…Parallel studies investigating fish abundance changes in the Penobscot River after dam removal have also found an increase in fish abundance and species richness after dam removal. Kiraly, Coghlan, Zydlewski, and Hayes (2015) and Watson (2017) conducted electrofishing surveys from 2010 to 2012 (before dam removal) and 2014 to 2015 (after dam removal) to study fish assemblages in the main stem and tributaries. They found that river reaches that underwent habitat and connectivity changes after dam removal displayed a 31% average increase in Morisita-Horn's species similarity index that was attributed to increased habitat access for diadromous fishes (Watson, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parallel studies investigating fish abundance changes in the Penobscot River after dam removal have also found an increase in fish abundance and species richness after dam removal. Kiraly, Coghlan, Zydlewski, and Hayes (2015) and Watson (2017) conducted electrofishing surveys from 2010 to 2012 (before dam removal) and 2014 to 2015 (after dam removal) to study fish assemblages in the main stem and tributaries. They found that river reaches that underwent habitat and connectivity changes after dam removal displayed a 31% average increase in Morisita-Horn's species similarity index that was attributed to increased habitat access for diadromous fishes (Watson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kiraly, Coghlan, Zydlewski, and Hayes (2015) and Watson (2017) conducted electrofishing surveys from 2010 to 2012 (before dam removal) and 2014 to 2015 (after dam removal) to study fish assemblages in the main stem and tributaries. They found that river reaches that underwent habitat and connectivity changes after dam removal displayed a 31% average increase in Morisita-Horn's species similarity index that was attributed to increased habitat access for diadromous fishes (Watson, 2017). Furthermore, an increase in total abundance for alewife, American shad, American eel, sea lamprey, and striped bass was observed at the respective lowermost dam in both predam and postdam removal years (Veazie Dam 2010-2013and Milford Dam 2015-2016Simpson, Mitchell, Maine Department of Marine Resources, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat restoration for threatened species (e.g. for coho salmon; Wright & Souder, ) and landscape restoration measures for whole‐ecosystem recovery, as in the Penobscot River (Watson, Coghlan, Zydlewski, Hayes, & Kiraly, ), have a long tradition in North America (Bernhardt et al, ) and globally (Wohl, Lane, & Wilcox, ). Optimization‐based systematic approaches to restoration planning are not as established as their counterparts in conservation science, though.…”
Section: Advancing Conservation Prioritizations To Inform Integrated mentioning
confidence: 99%
“…Current interest in the status of alewives and the success of dam removal and improved fish passage in increasing alewife abundance, particularly in Maine [26,27], encouraged us to test, via ecosystem modeling, the impacts of increasing anadromous forage fish populations on marine food webs. First, we estimated potential alewife production in three Maine watersheds (Androscoggin, Kennebec, and Penobscot) based on the spawning habitat potentially available to them.…”
Section: Introductionmentioning
confidence: 99%